Genetic Susceptibility to Lipid Levels and Lipid Change Over Time and Risk of Incident Hyperlipidemia in Chinese Populations. (February 2016) - Lu, Xiangfeng; Huang, Jianfeng; Mo, Zengnan; He, Jiang; Wang, Laiyuan; Yang, Xueli; Tan, Aihua; Chen, Shufeng; Chen, Jing; Gu, C. Charles; Chen, Jichun; Li, Ying; et al.
Abstract : Background—: Multiple genetic loci associated with lipid levels have been identified predominantly in Europeans, and the issue of to what extent these genetic loci can predict blood lipid levels increases over time and the incidence of future hyperlipidemia remains largely unknown. Methods and Results—: We conducted a meta-analysis of genome-wide association studies of lipid levels in 8344 subjects followed by replication studies including 14 739 additional individuals. We replicated 17 previously reported loci. We also newly identified 3 Chinese-specific variants in previous regions ( HLA-C, LIPG, and LDLR ) with genome-wide significance. Almost all the variants contributed to lipid levels change and incident hyperlipidemia >8.1-year follow-up among 6428 individuals of a prospective cohort study. The strongest associations for lipid levels change were detected at LPL, TRIB1, APOA1-C3-A4-A5, LIPC, CETP, and LDLR ( P range from 4.84×10 −4 to 4.62×10 −18 ), whereas LPL, TRIB1, ABCA1, APOA1-C3-A4-A5, CETP, and APOE displayed significant strongest associations for incident hyperlipidemia ( P range from 1.20×10 −3 to 4.67×10 −16 ). The 4 lipids genetic risk scores were independently associated with linear increases in their corresponding lipid levels and risk of incident hyperlipidemia. A C -statistics analysis showed significant improvement in the prediction of incident hyperlipidemia on top of traditional risk factors including the baseline lipid levels. Conclusions—: These findings identified some evidence for allelic heterogeneity in Chinese when compared with Europeans in relation to lipid associations. The individual variants and those cumulative effects were independent risk factors for lipids increase and incident hyperlipidemia. Abstract : Supplemental Digital Content is available in the text.